ANALYSIS OF THE SIGMATISM TYPE OF SPEECH DEFECT OF DYSLALYIA.THE IMPORTANCE OF TRAINING ANDDIDACTIC GAMES IN ELIMINATING SPEECH DEFECTS IN CHILDREN (Universal International Scientific Journal, 2026)
This article discusses one of the speech defects, the sigmatism type of dyslalia. Sigmatism, that is, the confusion of the sounds "S" and "Z" or the alternation of both sounds, and how this situation is pronounced in the child's articulatory apparatus, is presented, along with the implementation of correction work specific to the sigmatism type of dyslalia. The role of didactic games and several interesting exercises in the development of a child's speech, not only in this speech defect, but also in eliminating all speech defects, is given, as well as information on how to apply these games and exercises to children. In addition, extensive information is provided on the importance of play activity in the development of a child and how to study it in close connection with speech development, and precisely from this aspect, the maximum development of a child's speech and the formation of correct communication skills are provided.
Keywords: Dyslalia; Sigmatism; Articulation profile